2016
DOI: 10.15689/ap.2015.1403.02
|View full text |Cite
|
Sign up to set email alerts
|

Validity evidence of the Portuguese version of the Interpersonal Reactivity Index for Couples

Abstract: -Validity evidence of the Portuguese version of the Interpersonal Reactivity Index for CouplesThe main objective of this study was to translate and adapt the Interpersonal Reactivity Index for Couples (IRIC) to Portuguese, and analyze the psychometric properties of the Portuguese version. This instrument that assesses empathy in couples, resulted from the adaptation of one of the most widely used empathy scales -Davis´s Interpersonal Reactivity Index -for the context of intimate relationships. The IRIC assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 40 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…The score of dyadic perspective taking can vary between 0 and 24 and the score of dyadic empathic concern can vary between 0 and 28. The Portuguese version of IRIC showed adequate internal consistency values (Cronbach’s α = 0,82) and good levels of external validity with a dyadic adjustment scale (DAS) 72 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The score of dyadic perspective taking can vary between 0 and 24 and the score of dyadic empathic concern can vary between 0 and 28. The Portuguese version of IRIC showed adequate internal consistency values (Cronbach’s α = 0,82) and good levels of external validity with a dyadic adjustment scale (DAS) 72 .…”
Section: Methodsmentioning
confidence: 99%
“…To assess dyadic empathy, participants completed the Portuguese version of the Interpersonal Reactivity Index for Couples (IRIC) 24,72 . The IRIC is a modified version of the Interpersonal Reactivity Index (IRI) that assesses cognitive and emotional empathy in the context of intimate relationships.…”
Section: Methodsmentioning
confidence: 99%
“…Peloquin and Lafontaine (2010) constructed the scale based on three Canadian samples, composed of participants involved in a heterosexual or in a homosexual romantic relationship, and on a group of heterosexual romantic couples. The two-factor model of the IRIC was confirmed in a Portuguese sample of participants who were in romantic relationships ( Coutinho et al, 2015 ), in two Chilean samples of individuals involved in romantic relationships (Guzman Gonzalez et al, 2014) and in a sample of Iranian couples ( Ramezani et al, 2019 ). Good psychometric properties were indicated and were better for dyadic perspective taking in the original version, whereas in Chile dyadic empathic concern did not show proper internal consistency.…”
Section: Introductionmentioning
confidence: 79%
“…Good psychometric properties were indicated and were better for dyadic perspective taking in the original version, whereas in Chile dyadic empathic concern did not show proper internal consistency. However, all previous studies indicated that the IRIC is a valid measure as both dyadic empathy factors were associated with general empathic concern and general perspective taking, and with a higher level of romantic satisfaction ( Coutinho et al, 2015 ; Peloquin & Lafontaine, 2010). There were significant associations between two dyadic dimensions and between assessments of both partners in a romantic couple (Peloquin & Lafontaine, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation